OUTLOOK ON BASIC EDUCATION QUALITY IMPROVEMENT - Burhanuddin Tola (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2014)
This study aims to explore an outlook of future quality basic education by deploying reference analysis varied sorts of resources. The analysis was conducted by analyzing current condition of improvement and enhancement of the learning access and opportunities of all primary school-aged children who reach Minimum Participation Rate (MPR) of 100% by 2015. This involved less economically developed, people living in remote, border and isolated areas and districts. Current and future analysis suggests the quality education lies not merely on achieving the MPR indicators of 100% along with the reduction of the percentage of students’ learning period and the number of dropouts and retakes, but also on analyzing the periodical competence benchmark on the literacy achievement of Indonesian children. The achievement is greatly influenced by economic growth illustrated in Gross National Income (GNI) and Gross Domestic Product (GDP). This study found that future basic education quality significantly affect the economic growth of Indonesia. Keywords: outlook of basic education, periodical competence benchmark, literacy achievement, GNI/GDP.